Teach yourself visually complete Excel 2013 - McFedries, Paul (John Wiley & Sons, Inc., 2013)
Get the basics of Excel and then go beyond with this new instructional visual guide While many users need Excel just to create simple worksheets, many businesses and professionals rely on the advanced features of Excel to handle things like database creation and data analysis. Whatever project you have in mind, this visual guide takes you step by step through what each step should look like. Veteran author Paul McFedries first presents the basics and then gradually takes it further with his coverage of designing worksheets, collaborating between worksheets, working with visual data.